Early Childhood Care and Education / International Perspectives - Melhuish Edward; Petrogiannis Konstantinos (Rouledge, 2006)
Introducing International Perspectives on Early Childhood Care and Education, Childcare in the United States: Characteristics and Consequences, Policy and Research on Early Childcare and Education in Greece, Policy and Research on Preschool Care and Education in the UK, Children's and Parents' Needs and Early Education and Care in Italy, Policy and Research on Childcare in Sweden, Early Childhood Care and Education in Israel, Early Childhood Care and Education: An Indian Perspective, Development of Kindergarten Care and Education in the People's Republic of China since the 1990's, An International Overview of Early Childhood Care and Education, Index.